2008
DOI: 10.1002/cmdc.200800110
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Solvent Accessibility Epitopes for Different Dehydrogenase Inhibitors

Abstract: Knowledge about the orientation of ligands or inhibitors bound to a protein is vital for the development of new drugs. It was recently shown that solvent accessibility epitopes for protein ligands can be mapped by transferring magnetization from water molecules to the ligand to derive the ligand orientation. This is based on the fact that NMR signals of ligands arising from magnetization transferred from solvent molecules via the protein have a different sign from those arising from direct magnetization transf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 27 publications
0
18
0
Order By: Relevance
“…Recently, Günther and coworkers have described a modified version of the experiment [187], denoted SALMON (Solvent accessibility, ligand binding, and mapping of ligand orientation by NMR spectroscopy), that applied using small mixing times for protein-mediated magnetization transfer allows the mapping of binding epitopes on the ligand. Several recent applications have been described using such modified experiment [188][189][190]. Besides, a recent optimization of the pulse sequence results in significantly reduced NMR acquisition times [191].…”
Section: Waterlogsymentioning
confidence: 99%
“…Recently, Günther and coworkers have described a modified version of the experiment [187], denoted SALMON (Solvent accessibility, ligand binding, and mapping of ligand orientation by NMR spectroscopy), that applied using small mixing times for protein-mediated magnetization transfer allows the mapping of binding epitopes on the ligand. Several recent applications have been described using such modified experiment [188][189][190]. Besides, a recent optimization of the pulse sequence results in significantly reduced NMR acquisition times [191].…”
Section: Waterlogsymentioning
confidence: 99%
“…The most commonly used techniques which observe ligand resonances employ magnetization transfer by the nuclear Overhauser effect (NOE). These include the transferred NOE (19), NOE pumping (20) and reverse pumping (21), saturation transfer (STD-NMR) (22)(23)(24), waterLOGSY (25,26), derivation of solvent accessibility epitopes from waterLOGSY experiments (SALMON) (27,28) and interligand NOEs between two competitively binding molecules (INPHARMA) (29,30).…”
Section: Tins Excess Yes No Yesmentioning
confidence: 99%
“…While the initial waterLOGSY experiment seemed to be limited to the identification of binders vs non-binders recent work showed that waterLOGSY can be used to probe for bulk water accessibility to derive the orientation of a bound ligand. This approach has been termed SALMON (Solvent Accessibility and protein Ligand binding studied by NMR Spectroscopy) (27,28). To be able to derive a solvent accessibility epitope from waterLOGSY spectra shorter mixing times have to be chosen to avoid blurring of of the epitope by massive spin diffusion.…”
Section: Waterlogsy and Salmonmentioning
confidence: 99%
See 1 more Smart Citation
“…Particularly, in early stages of the FBLD process where often medium-to-weak binders are encountered, NMR spectroscopy is particularly powerful as it is not only a very sensitive detection technique but also provides additional information about binding modes and orientations of bound ligands (mapping of the binding site). Several experiments have thus been developed in the recent past (INPHARMA 9 and SALMON 10 ). Most recently, we have devised an NMR pulse sequence for the investigation of protein ligand interactions.…”
Section: Introductionmentioning
confidence: 99%